Pelatihan pembuatan desain batik motif melayu bagi guru dan siswa SMPS Adhyaksa Medan - Wahyu Tri Atmojo; Misgiya Misgiya; Hidayat Hidayat; Alifia Azzahra; Daffarul Khusaini Nasution (SELAPARANG: Jurnal Pengabdian Masyarakat Berkemajuan, 2025)
AbstrakPelatihan pembuatan desain batik motif Melayu ini diselenggarakan sebagai salah satu upaya pelestarian budaya lokal sekaligus pengembangan keterampilan seni bagi guru dan siswa di SMPS Adhyaksa Medan. Pelatihan yang dilaksanakan ini bertujuan untuk meningkatkan pemahaman siswa dan guru terhadap nilai-nilai budaya Melayu melalui eksplorasi motif tradisional serta memperkenalkan teknik dasar dalam mendesain batik baik secara kreatif maupun aplikatif. Metode pelatihan yang diterapkan meliputi penyampaian materi secara teoritis mengenai sejarah dan filosofi motif Melayu, teknik refleksi desain batik, serta praktik langsung yang melibatkan peserta secara aktif. Hasil pelatihan menunjukkan peningkatan pengetahuan peserta terhadap motif batik tradisional serta kemampuan mereka dalam menghasilkan desain batik yang asli dan diabadikan pada identitas budaya lokal, hal itu ditandai dengan 32 karya batik motif Melayu hasil dari peserta pelatihan yang akan dipamerkan di sekolah SMPS Adhyaksa Medan. Sehingga, dengan dilaksanakannya pelatihan ini diharapkan menjadi salah satu langkah awal bagi guru dan siswa dalam membangun kesadaran dan melestarikan budaya serta menumbuhkan semangat wirausaha. Kata kunci: desain; motif; batik; etnis melayu. AbstractTraining this batik design training for Malay motifs was organised as one of the efforts to preserve local culture as well as develop art skills for teachers and students at SMPS Adhyaksa Medan. teachers and students at SMPS Adhyaksa Medan. The training that was conducted aims to increase students‘ and teachers’ understanding of the values of values through the exploration of traditional motifs as well as introducing basic techniques in designing batik both creatively and techniques in batik design both creatively and applicatively. Training methods method applied included the delivery of theoretical material on the history and philosophy of Malay and philosophy of Malay motifs, batik design reflection techniques, as well as hands-on practice that actively involved the participants. that actively involved the participants. The results of the training showed an increase in participants' knowledge of traditional batik motifs as well as their ability in producing batik designs that are original and immortalised in the local cultural identity, as marked by the 32 batik designs produced by the participants. It was characterised by 32 batik works of Malay motifs produced by the training participants that will be exhibited at the school. that will be exhibited at SMPS Adhyaksa Medan. Thus, with the implementation of this training is expected to be one of the first steps for teachers and students in building awareness and perpetuating local cultural identity. teachers and students in building awareness and preserving culture as well as fostering an entrepreneurial spirit. foster an entrepreneurial spirit. Keywords: design; motif; batik; malay ethnicity